Improved blastocyst development of single cow OPU-derived presumptive zygotes by group culture with agarose-embedded helper embryos - Dey Shukla; Bang Jae; Choi Byung; Kwon Tae; Jin Jong; Deb Gautam; Cho In; Kong Il Keun (BMC, 2011)
Abstract Background The in vitro culture of presumed zygotes derived from single cow ovum pick-up (OPU) is important for the production of quality blastocysts maintaining pedigree. The aim of the present study was to evaluate the agar chip-embedded helper embryo coculture system for single cow OPU-derived zygotes by assessing embryo quality. Methods Cumulus oocyte complexes (COCs) were collected from Hanwoo cows with high genetic merit twice a week using the ultra-sound guided OPU technique and from slaughterhouse ovaries. The Hanwoo cow COCs and slaughterhouse ovaries were matured in vitro, fertilized in vitro with thawed Hanwoo sperm and cultured for 24 h. The presumed zygotes were subsequently placed in three different culture systems: (1) control OPU (controlOPU) with single cow OPU-derived presumed zygotes (2~8); (2) agar chip-embedded slaughterhouse helper embryo coculture (agarOPU) with ten presumed zygotes including all presumed zygotes from a cow (2~8) and the rest from agar chip-embedded slaughterhouse presumed zygotes (8~2); and (3) slaughterhouse in vitro embryo production (sIVP) with ten slaughterhouse ovary-derived presumed zygotes, each in 50 μL droplets. Day 8 blastocysts were assayed for apoptosis and gene expression using real time PCR. Results The coculture system promoted higher blastocyst development in OPU zygotes compared to control OPU zygotes cultured alone (35.2 vs. 13.9%; P < 0.01). Genes predicted to be involved in implantation failure and/or embryo resorption were down-regulated (P < 0.05) in control OPU zygotes (CD9, 0.4-fold; AKRAB1, 0.3-fold) and in cocultured zygotes (CD9, 0.3-fold; AKRAB1, 0.3-fold) compared to sIVP blastocysts (1.0-fold). Moreover, genes involved in implantation and/or normal calf delivery were up-regulated (P < 0.05 to P < 0.01) in control OPU zygotes (PGSH2, 5.0-fold; TXN, 4.3-fold; PLAU, 1.7-fold) and cocultured zygotes (PGSH2, 14.5-fold; TXN, 3.2-fold; PLAU, 6.8-fold) compared to sIVP (1.0-fold) blastocysts. However, the expression of PLAC8, TGF-β1, ODC1, ATP5A1 and CASP3 did not differ between the three culture groups. Conclusions Results show that the agar chip-embedded helper embryo coculture system enhances developmental competence and embryo quality in cultures of limited numbers of high pedigree single cow OPU presumed zygotes.